Aplicaciones del Bacillus y Trichoderma en la agroindustria (Agroindustria, Sociedad y Ambiente, 2022)
This essay aims to create a reflection of the food crisis we are experiencing and how biotechnology represents a viable alternative to tackle this serious crisis that, according to the FAO, would worsen in the coming decades. It focuses on the review of recent scientific articles to carry out a comparative analysis considering the use, applications, advantages and impacts of microorganisms such as Bacillus thuringiensis and Trichoderma as biocontrollers and as producers of glucoamylase enzymes for the production of bioethanol from agro-industrial waste.
Keywords: Biocontrollers; Glucoamylases; Bioethanol.